2022
DOI: 10.3389/fpubh.2022.853041
|View full text |Cite
|
Sign up to set email alerts
|

Research on Knowledge, Attitudes, and Practices of Influenza Vaccination Among Healthcare Workers in Chongqing, China—Based on Structural Equation Model

Abstract: BackgroundInfluenza is associated with a large number of disease burdens, and it is generally recommended that all healthcare workers (HCWs) get an influenza vaccination. However, the vaccination rates among HCWs are still low. This study aimed to assess HCWs' knowledge, attitude, and practice (KAP) about the influenza vaccine, and by establishing a structural equation model (SEM) to explore the influencing factors of medical personnel's influenza vaccination in Chongqing, China.MethodsFrom September to Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Surprisingly, a negative association between knowledge about HPV and intention to receive HPV vaccine was found in the results, which was contrary to prior studies ( 36 ). Firstly, some authors have speculated that this may be related to individual knowledge about relevant side-effects or adverse reactions of vaccines.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, a negative association between knowledge about HPV and intention to receive HPV vaccine was found in the results, which was contrary to prior studies ( 36 ). Firstly, some authors have speculated that this may be related to individual knowledge about relevant side-effects or adverse reactions of vaccines.…”
Section: Discussioncontrasting
confidence: 99%
“…On the topic of vaccination, Chen et al ( 36 ) investigated influenza vaccination among healthcare workers in Chongqing and noted that influenza-related knowledge was positively associated with attitude and vaccination practice, with a strong mediating effect of attitude between knowledge and practice. In a survey on the current knowledge, attitude and practice of HPV vaccination among female college students in Hong Kong, Leung and Law ( 37 ) found that female college students with high HPV vaccine knowledge and positive attitude toward HPV vaccine were more likely to receive the HPV vaccine.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Moreover, the study found that attitude mediated between knowledge and practice, indicating that attitude influenced knowledge translation into behavior. These findings were consistent with the KAP theoretical model and previous findings [ 29 , 30 ]. According to the KAP model, dietary behavioral changes in HD patients involved three successive processes: knowledge acquisition, belief generation, and behavior formation.…”
Section: Discussionsupporting
confidence: 93%
“…Influenza is an overlooked contributor to morbidity and mortality ( 40 42 ). Several studies assessed knowledge about influenza and attitudes toward its vaccine among healthcare professionals ( 43 50 ). However, studies to assess the same among the public are generally scarce ( 46 , 51 53 ), especially in a low-income, war-torn developing country such as Yemen.…”
Section: Discussionmentioning
confidence: 99%